Evaluacion de nueva tecnologia de frijol a nivel de finca sur de Huila, Colombia, 1978-1980 - Ruíz de Londoño, Norha; Sanders, J.H.; Pachico, Douglas H.; Herrera Durán, O. (International Center for Tropical Agriculture, 1985)
On-farm research results of 3 yr evaluating new bean technology (var. and cultural practices) at Pitalito, Suaza, and Timana in southern Huila, Colombia, are presented. Clean seed, insecticides, increased plant density, fertilizers, and new var. for both monocropped and associated (maize) beans were the components evaluated. No response was observed to the use of fertilizers, especially P. Farmer seed produced yields as high as those obtained from clean seed. Increased yields and net income/ha were obtained with the use of pesticides together with higher plant densities and intensive weed control. Yields increased 66-85 percent compared with farmer technology; however, returns to investments did not increase significantly since total costs also increased with improved technology. Var. ICA L-24 outyielded the local var. Calima with insecticides and fungicides. The net income/ha was 2-3 times higher for the bean/maize association than for monocropped beans. (CIAT)